Complex strain evolution of polar and magnetic order in multiferroic BiFeO3 thin films - Zuhuang Chen (Nature Portfolio, 2018)
To fully exploit the potential of multiferroic materials the control of their intrinsic degrees of freedom is a prerequisite. Here, the control of spin orientation in strained BiFeO3 films is demonstrated elucidating the microscopic mechanism of the complex interplay of polar and magnetic order.